Riparian Lowlands in Clay Till Landscapes Part II: Nitrogen Reduction and Release Along Variable Flow Paths. Issue 4 (8th April 2020) - Petersen, R. J.; Prinds, C.; Jessen, S.; Iversen, B. V.; Kjaergaard, C.
Abstract: Riparian lowlands are known to control catchment nitrogen (N) balances. This study examined the role of agricultural tile drainage systems, often present in clay till landscapes, on the transport, transformation, and mass balance of N species in four riparian peat lowland transects receiving agricultural tile drainage water. Monitoring of N speciation of drain, stream, and groundwater, combined with a previously established water balance, enabled the determination of N mass balances for different flow paths including groundwater, subsurface drain water, and overland flow for each piezometer transect. The type of overland flow largely affected nitrate‐N (NO3 ‐N) removal efficiency, as determined by the total N output from a transect relative to the NO3 ‐N loading (%). Infiltration and subsurface flow followed by exfiltration (short return flow) allowed an efficient removal of NO3 ‐N (71–94%), while direct overland flow strongly lowered NO3 ‐N removal (25%) in one transect. The hydraulic loading rate versus the lowland infiltration capacity determined the transport pathways and thus the resulting NO3 ‐N removal efficiency. For all transects there was a net export of organic N and/or ammonium, associated with in situ N release from peat decomposition, through overland flow and groundwater discharge. These exports partly counterbalanced NO3 ‐N removal and significantly reduced the overall total N removal for the riparian lowlands. However, the N removal efficiencies remained positive (1–56%). The study indicates that N budgets for riparian lowlands need to account for overland flow as a transport pathway for N. Key Points: Nitrate (NO3 − ) removal in riparian lowlands (RLs) depends on the infiltration of NO3 − into organic riparian lowland sediments. Direct overland flow, bypassing the RL soil and sediment, decreases nitrate removal. RLs may be sinks or sources of nitrogen (N) depending on the balance between removal of nitrate and release of ammonium and organic N.